Improving disease management of patients with inflammatory bowel disease: the potential role of self-concordant health goals - Horvát, Barbara; Dávid, Anett; Sallay, Viola; Rafael, Beatrix; Njers, Sanela; Orbán, Kata; Molnár, Tamás; Csabai, Márta; Martos, Tamás (Frontiers in Psychology, 2023)
Inflammatory bowel diseases (IBD) are chronic gastrointestinal conditions that significantly impact patients’ quality of life. Previous research indicates that patients with IBD have a higher prevalence of anxiety compared to the general population and other chronic diseases. This pilot study aimed to investigate the relationships between goal integration, positive and negative emotions, goal self-efficacy, and trait anxiety as the outcome variable, focusing on patients’ self-management strategies. Drawing from the Self-Concordance Model (SCM) of Self-Determination Theory (SDT), the study explored how goal integration is associated with more fulfilling and enjoyable experiences and fewer negative emotions, ultimately improving psychological well-being. Health-related goals were evaluated using the Personal Project Analysis technique, while the State–Trait Anxiety Inventory was utilized to measure general anxiety levels. Among the 141 participants with inflammatory bowel disease, 96 reported having health-related goals. Of these, 66 were female (68.75%), and 30 were male participants (31.25%). Path analysis revealed a moderate negative association between self-concordance (SC) and negative emotions, which, in turn, predicted higher levels of trait anxiety. Furthermore, the alternative model tested indicated that trait anxiety predicted a lower level of self-concordance. Setting well-integrated health goals involves an internal capacity, enabling patients to experience less negative emotions during self-management activities. Anxiety can hinder individuals from accessing their inner needs, resulting in less self-concordant aspirations and more negative emotions. These findings may contribute to developing prevention and intervention programs to enhance IBD patients’ adherence to lifestyle changes, ultimately improving their overall well-being.